Association of systemic lupus erythematosus and choriocarcinoma: A role of hormonal immunomodulation? (1993)
We report the first case of choriocarcinoma occurring during the course of systemic lupus erythematosus (SLE). This choriocarcinoma was revealed by pulmonary metastasis associated with pulmonary hypertension secondary to neoplastic thrombi and pulmonary embolism, in parallel to a flare up of the SLE. The role of hormones in SLE is discussed.